O pecado original doméstico: uma análise da experiência brasileira entre 2001 a 2016 - Oliveira, Édivo de Almeida (2017)
The main structural characteristic of the International Monetary System (IMS) is its highly hierarchical character, the consequences of which are manifested themselves within the economic system. In the less developed economies, in particular, these consequences may occur in the form of "weak" or inconvertible currencies, less financing opportunities through the financial market and greater instability of capital flows, as well as deterioration of the level of internal autonomy regarding the use of economic policies in the process of development and macroeconomic stability of each national economy. Among the phenomena that unfold from the hierarchy of national currencies is the original domestic sin, which is related to the difficulty that some countries present in the issuance of public debt bonds in the domestic market denominated in local currency and which are simultaneously fixed and long-term. Among the negative consequences of this phenomenon are the mismatch of liabilities and assets of public accounts and the deterioration of the government's solvency capacity in the presence of exchange devaluations or high interest rates and inflation. In addition to seeking to overcome the domestic original sin in Brazil, the present study has it is importance backed by the fragility of the Brazilian currency in the international hierarchy and, consequently, it’s greater exposure to risk and dysfunctions that result from it. The objective of this study is to calculate the indices referring to domestic original sin between 2001 and April 2016 in the Brazilian federal securities market. For this, the calculation of three distinct and complementary indices formulated by Hausmann and Panizza (2003) were used. Among the results obtained, it was possible to verify that the reduction of the external public debt burden was carried out at the cost of the substantial increase of the public indebtedness base through the securities market. It is also observed that in the period evaluated the federal public securities market in Brazil experienced significant transformations. However, domestic federal securities debt is currently heavily indexed to inflation and with significant participation of low maturity fixed rate securities, as well as maintaining a considerable portion of SELIC indexed securities. It was evidenced by the results of the indices that the measures implemented by the Federal Government throughout the decade of 2000, led to a change in the form of manifestation of original domestic sin, however, without any sensible change in its acute magnitude in the Country.